2017
DOI: 10.5812/pedinfect.61630
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic Prescribing Pattern in Neonates of Seventeen Iranian Hospitals

Abstract: Background: The association between the use of antibiotics and bacterial resistance has obviously been established and it seems to be a significant problem for public health. It is clear that irrational use and high rates of antibiotic prescription are associated with increased bacterial resistance. As antibiotics are the class of drugs commonly prescribed in neonatal and Neonatal Intensive Care Unit (NICU) wards, neonates are at high risk of opportunistic or nosocomial infections due to prolonged hospitalizat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 20 publications
1
10
0
2
Order By: Relevance
“…This study showed that the rates of antibiotic uses were high in the pediatric and neonatal wards of two tertiary teaching hospitals located in two different provinces of Iran (61% and 71%, respectively), which is consistent with two multicenter studies from Iran (8,9). This rate in hospitalized children was significantly higher in the BTH (72%) than in the NTH (56%; P =0.03).…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…This study showed that the rates of antibiotic uses were high in the pediatric and neonatal wards of two tertiary teaching hospitals located in two different provinces of Iran (61% and 71%, respectively), which is consistent with two multicenter studies from Iran (8,9). This rate in hospitalized children was significantly higher in the BTH (72%) than in the NTH (56%; P =0.03).…”
Section: Discussionsupporting
confidence: 89%
“…Such variations may be partly due to differences in hospital systems and patients. Next, in a recent study from Iran, the rate of antibiotic use was high (66.6%), compared to other countries (8,9). As reported, a more frequent and inappropriate use of antibiotics has contributed to higher levels of emerging antimicrobial resistance (20,21).…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…This result is in contrast to other studies [24,28,49,50,51,52]. Several studies have reported high rate of irrational antibiotic prescription and a significant percentage of them were empirically prescribed for patients [26,41,53,54].…”
Section: Discussionmentioning
confidence: 65%